Photolysis Technology Application to Overcome the Lack of Water in the Countryside - Firra Rosariawari; Iwan Wahjudijanto; Novirina Hendrasarie (Future Science)
Sendang was a village of Subdistrict Penanggungan Trawas Mojokerto, that has ground water source. However, with its rapidly increasing population growth, it made bad impact for the quality of water resources. Disposal of garbage and animal husbandry activities that were above the water source, has a contribution as a polluter of water resources. Escherichia coli was an important parameter as an indication of contamination of ground water or potable water. By providing knowledge and technology for the people of Sendang, helped them to get ground water. Photolysis technology applied in Sendang was a disinfection technology. The process kills bacteria by using ultra violet light. The energy used to power the ultra violet light is derived from solar energy. Solar Cell used to capture solar energy which is then stored into the dry battery (batteries) to provide energy in ultra violet light. So the villagers are not burdened by the cost of electricity for this technology. Disinfectant process by using photolysis technology could removal E. coli bacteria till 75 % for 80 minutes. Removal of E. coli increased by exposure of Ultra violet on long time.